Child labour in agriculture: Madagascar's plans - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1999)
Madagascar is the first country in French-speaking Africa to commit itself to abolishing child labour. In June 1998, the Malagasy government signed an agreement for a three-year national plan of action with the International Labour Office in Geneva....